2015
DOI: 10.1159/000437268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Treatment with Estradiol and Estrogen Receptor Subtype Agonists on Serotonergic Function in Ovariectomized Rats

Abstract: Acute estradiol treatment was reported to slow the clearance of serotonin via activation of estrogen receptors (ER)β and/or GPR30 and to block the ability of a selective serotonin reuptake inhibitor (SSRI) to slow serotonin clearance via activation of ERα. In this study, the behavioral consequences of longer-term treatments with estradiol or ER subtype-selective agonists and/or an SSRI were examined in the forced swim test (FST). Ovariectomized rats were administered the following for 2 weeks: estradiol, ERβ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 77 publications
(83 reference statements)
1
24
0
2
Order By: Relevance
“…In 4-month OVX rats, it was shown previously that long-term E 2 (5 μg) induced an AD-like effect in the FST (Benmansour et al, 2016). In 10-month OVX rats, E 2 (5 μg) did not change immobility or swimming behavior in the FST as compared to that measured in control rats (data not shown).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In 4-month OVX rats, it was shown previously that long-term E 2 (5 μg) induced an AD-like effect in the FST (Benmansour et al, 2016). In 10-month OVX rats, E 2 (5 μg) did not change immobility or swimming behavior in the FST as compared to that measured in control rats (data not shown).…”
Section: Resultsmentioning
confidence: 77%
“…We have selected a dose of sertraline that has been shown not only to downregulate the SERT but also to produce AD-like effects in the FST when given chronically to male rats (Benmansour et al, 1999; Bilge et al, 2008; Furmaga et al, 2011) as well as to female OVX rats (Benmansour et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK1/2 has been implicated in several biological functions. ERK1/2 are highly expressed in different brain regions, including the hippocampus, amygdala, and the prefrontal area, supporting the putative effect of ERK1/2 on maintaining neuroplasticity (Benmansour, Adeniji, Privratsky, & Frazer, ; Dwivedi, Rizavi, Roberts, Conley, & Pandey, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 72%
“…Several investigators have reported that decreased BDNF or ERK in a chronic‐stress model of depression could lead to impaired neurogenesis and depressive symptoms (Benmansour et al, ; Dwivedi et al, ; Liu et al, ; Pochwat et al, ; Zhang et al, ). Based on these studies, the effect of CUR on aromatase enzyme and the factors responsible for neuroplasticity, BDNF and ERK1/2 were evaluated in the limbic system relative to E 2 as a hormonal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%